2014
DOI: 10.1097/ans.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Discrimination and Children's Mental Health Symptoms

Abstract: Perceived discrimination has been shown to be strongly associated with mental health outcomes, such as depression, anxiety, chronic stress, post traumatic stress disorder, and low self-esteem. This study (N = 88) examined the effects of perceived discrimination and its association with child mental health symptoms. African American children had a significantly stronger association between social stress and a sense of exclusion/rejection than Multiracial or European American children. Nurses need to assess and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Perceived discrimination negatively affects psychological wellbeing and mental health (Cokley et al, 2012;Fernández et al, 2014;Goldman et al, 2008;Williams et al, 2012). Cooke, Bowie, & Carrère (2014) results that perceived discrimination makes higher chronic stress, lower self-esteem, depression, anxiety and post-traumatic stress disorder. Many research showed about negative outcomes of perceived discrimination.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Perceived discrimination negatively affects psychological wellbeing and mental health (Cokley et al, 2012;Fernández et al, 2014;Goldman et al, 2008;Williams et al, 2012). Cooke, Bowie, & Carrère (2014) results that perceived discrimination makes higher chronic stress, lower self-esteem, depression, anxiety and post-traumatic stress disorder. Many research showed about negative outcomes of perceived discrimination.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Extending from the aforementioned news headlines, researchers have found that Black youth are frequently exposed to prejudice and discrimination based on race, with recent reports suggesting these youth experience more than five incidents daily on average (English et al, 2020). Generally, Black youth experiencing racial discrimination are at risk of more internalizing symptoms, including symptoms of depression (Benner et al, 2018; Greene et al, 2006; Priest et al, 2013) anxiety, and stress (Cooke et al, 2014; Walker et al, 2017) as well as negative behavioral (DuBois et al, 2002) and educational (e.g., Jelsma & Varner, 2020) wellbeing outcomes. Another, relatively less investigated consequence of racism for Black youth concerns internalized racial oppression (IRO) 1 : the adoption of racist ideology, stereotypes, and beliefs of inferiority into one’s psyche, as well as the extent to which a person may accept their marginalized status as justified, natural, and inevitable (Banks & Stephens, 2018; Shellae Versey et al, 2019).…”
Section: Racism’s Impact On Black Youth: Psychosocial Consequences An...mentioning
confidence: 99%
“…Unfortunately, the experience of gendered racism is not bounded by developmental epoch, as Black girls grow up facing gendered racism on multiple fronts: via police brutality [such as 15-year-old Dajerria Becton, who was assaulted and unlawfully detained while attending a pool party in Mckinney, Texas (Cole-Frowe & Fausset, 2015)] and 16-year-old Ma’Khia Bryant, who was shot and killed after she called police for help during an altercation (Carroll, 2021); inequitable school discipline practices [such as 16-year-old Ashlynn Avery, who was beaten and arrested for falling asleep in class (Charles, 2019)]; and discriminatory practices concerning appearance [such as 12-year-old Vanessa VanDyke, who was threatened with expulsion from an Orlando private school unless she changed the look of her natural hair (Charles, 2019)]. This exposure to racial and gendered oppression is related to negative emotional, psychological, and societal consequences (Benner et al, 2018; Cooke et al, 2014; Walker et al, 2017). In an effort to mitigate the negative effects of racism and sexism, Black families may be required to engage in multiple forms of socialization.…”
Section: Racism’s Impact On Black Youth: Psychosocial Consequences An...mentioning
confidence: 99%
“…To provide validity evidence based on correlation for the test scores calculated with different items, convergent validity evidence was analyzed, using information gathered using the Diagnostic Interview for Children (disc-iv; Shaffer, Fisher, Lucas, Dulcan, & Schwab-Stone, 2000), which is an instrument that evaluated 32 common psychiatric diagnoses of children based on the Diagnostic and Statistical Manual -iv (dsm-iv; Bell, 1994). Convergent validity evidence was also examined through correlations between the total score and children's reported physical health (Aarons et al, 2008), exposure to bullying or discrimination (Cooke, Bowie, & Carrère, 2014), and exposure to selected adversities (e.g., Anda et al, 2006). The latter includes exposure to factors such as community crime, parental separation, major sickness, and other stressful events, which have been widely linked to mental health problems during childhood.…”
Section: Se( θ | θ )= √I(θ)mentioning
confidence: 99%